O-12 Use of subcutaneous furosemide in the community setting in end-stage heart failure. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hodson, Fiona; Doyle, Chris; Karwatowski, Stefan; Albarjas, Mohammed; Ross, Joy
Abstract : Background: The benefits of integrated cardiac and palliative care support for patients with end-stage heart failure (ESHF) is well recognised (Jaarsma, Beattie, Ryder et al ., 2009; Hospice UK, 2017). Where patients are deteriorating or wish to avoid hospital, subcutaneous furosemide has been trialled to treat fluid overload resistant to oral diuretics (Zacharias, Raw, Nunn et al ., 2011). Methods: A case series is presented from a service evaluation of an integrated model of care for ESHF patients. 4/89 patients attended ambulatory hospital services for IV diuresis, 3/89 received IV/SC diuretics in the hospice. 13/89 were considered for continuous subcutaneous diuretics at home; this was administered to 7/13. Results: Average age 80 (±14) years. Four patients had left ventricular dysfunction, three had right sided heart failure. Average baseline eGFR 40 (22–70). Due to immobility and frailty, weight was not used to monitor outcome; blood pressure and renal functions supplemented clinical assessment. Average Systolic Blood Pressure 108 (±14) mmHg. Doses ranged between 80 mg and 230 mg of furosemide per 24 hours, depending on previous oral dose. 2 patients had subsequent dose reductions and 2 dose increments according to clinical response. Patients were treated for a median (range) 16 (1–48) days. 6/7 patients demonstrated symptom benefit. Three were successfully converted back to oral diuretics, one with addition of oral metolazone. One patient developed an abscess at the infusion site which necessitated A&E attendance and this subsequently healed well. There were challenges in supporting District Nurses to continue to administer and monitor infusions and in obtaining medication supplies from community pharmacy. Conclusion: Subcutaneous furosemide infusion in the community did improve symptomatic burden and improve quality of life in our patient group, avoiding hospital admission and enabling patients to spend quality time at home. Ongoing work is needed to further evaluate which patients will benefit most from this intervention.